Hadis Negasi Penularan Versus Perintah Phyisical Distancing: Singkronisasi Dakwah Di Masa Pandemi Antara Aqidah, Akhlak dan Medis - Lujeng Lutfiyah (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2020)
Almost every day, Corona has become a hot topic of conversation in various circles, both through the mass media and directly by word of mouth. The disease, which began to spread at the end of December 2020, is classified in the medical world as an infectious disease. This understanding is also circulating in the community.The widespread belief that there is a contagion on the one hand causes people to be careful in maintaining their health. But on the other hand, it resulted in very unfavorable conditions for those who happened to be victims. They are marginalized socially, and it is very logical that in reality there will also be marginalization in all other aspects of their lives.Therefore, this disease not only keeps the figures in the medical world busy, but also in the world of religious knowledge, especially in the field of the Prophet's hadith. This is because there are at least two traditions that talk about this kind of corona disease, one negates the transmission of the disease, while the other implies the opposite, namely an order to carry out physical distancing which indicates transmission.